Expertise and contributions. DAPA presentation to GCQRI - International Center for Tropical Agriculture; Läderach, Peter R.D.; Oberthür, Thomas; Lundy, Mark M.; Eitzinger, Anton; Bunn, Christian (2011)
With Presentations by Laure Collet, Robert Andrade, Henk van Rikxoort, Martin Wiesinger